Effects of maternal magnesium sulfate treatment on newborns. Issue 1 (17th December 2021) - Numoto, Shingo; Kakita, Hiroki; Takeshita, Satoru; Ueda, Hiroko; Kondo, Tomoko; Kurahashi, Hirokazu; Wakatsuki, Akihiko; Yamada, Yasumasa; Okumura, Akihisa
Abstract: Background: Antenatal magnesium sulfate (MgSO4 ) has been used with mothers, but the influence of MgSO4 on the fetus is unclear. The purpose of this study is to determine whether longer antenatal MgSO4 exposure correlates with adverse effects in newborns. Methods: The clinical data of 77 infants born to mothers treated with MgSO4 were collected. The infants were divided into two groups according to (1) the serum Mg concentration, (2) cumulative Mg dose, and (3) duration of antenatal maternal Mg treatment, respectively. Results: The serum Mg level of the infants correlated with that of the mothers but not with the duration of Mg treatment or the cumulative dose of Mg. There were no significant differences in the infants' clinical variables according to either the duration of Mg treatment or the cumulative dose of Mg. By contrast, enteral feeding tolerance began at a significantly later age and the heart rate on admission was significantly lower in infants with a serum Mg level ≥4.0 mmol/L than in those with a serum Mg level <4.0 mmol/L. Conclusions: Modest effects on the clinical variables of infants with higher serum Mg levels were determined, whereas neither the duration of Mg treatment nor the cumulative Mg dose correlated with the clinical variables of the infants. Thus, in newborns with only moderately elevated serum Mg levels, serious adverse effects are unlikely.